2010
DOI: 10.1021/ja909490r
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Photoluminescent Ag2S Quantum Dots from a Single Source Precursor

Abstract: Monodisperse Ag(2)S quantum dots (QDs) were synthesized via pyrolysis of Ag(DDTC) in oleic acid, octadecylamine, and 1-octadecene. The uniform alkyl-capped Ag(2)S QDs with a size of 10.2 nm emit near-IR emission at 1058 nm under 785 nm excitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
435
4
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 608 publications
(459 citation statements)
references
References 19 publications
12
435
4
8
Order By: Relevance
“…Likewise, NIR and SWIR bioimaging benefit NPs, which can interact efficiently with these wavelengths. [10][11][12] In the following, some important parameters and relevant examples with regard to EM-active NPs will be discussed. The definitions of NPs and nanomaterials are relatively broad, and thus, to simplify, this review will focus on (1) colloidal NPs based on inorganic materials and (2) some relevant bioapplications with regard to the interaction of NPs with EM fields, i.e., bioapplications based on EM-active NPs.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, NIR and SWIR bioimaging benefit NPs, which can interact efficiently with these wavelengths. [10][11][12] In the following, some important parameters and relevant examples with regard to EM-active NPs will be discussed. The definitions of NPs and nanomaterials are relatively broad, and thus, to simplify, this review will focus on (1) colloidal NPs based on inorganic materials and (2) some relevant bioapplications with regard to the interaction of NPs with EM fields, i.e., bioapplications based on EM-active NPs.…”
Section: Introductionmentioning
confidence: 99%
“…Different types of core/shell QDs (CdSe/ZnS, CdTe/ZnS, and CdTe/ ZnSe), core/shell/shell QDs (CdTe/CdS/ZnS and CdSe/ CdTe/ZnSe), and environmentally friendly QDs (CuInSe, Ag 2 S, and Si) have been synthesized for various purposes. [19][20][21][22][23][24][25][26][27][28] In our previous study, we reported that CdTe/ZnSe core/shell QDs can be applied for in vitro imaging of chicken tissue and embryo. 29 The biological applications of QDs can be hampered by their inherently low solubility in water.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, NIR-II fluorescence imaging can allow deep penetration into biological tissues with excellent imaging fidelity, sensitivity and resolution. [5][6][7] Over the past few years, considerable efforts have been devoted to develop high-quality NIR-II emitters including single-walled carbon nanotubes (SWNTs), [8][9][10] quantum dots (QDs), [11][12][13][14][15][16][17] rare-earth-doped nanoparticles (NPs), [18][19][20] and polymeric fluorophores. 21,22 Among them, the no toxic heavy metal-containing Ag2S QDs have become one of the most intensively studied NIR-II emitters.…”
Section: Introductionmentioning
confidence: 99%